Chemical Hydrophobization Of Materials (Diversity Research: Journal of Analysis and Trends, 2025)
In modern construction, one of the distinctive features of construction products and materials is their porosity, which leads to high moisture absorption. Rainwater can penetrate into the pores of materials, expanding several times at low temperatures and potentially causing their structural breakdown. Chemical treatments involve processes that create a dense, waterresistant layer on the surface of the material. One method to increase the density of a material's surface is by flotation. Impregnating porous stones with solutions based on monomers significantly enhances their durability.